2020
DOI: 10.1002/phar.2456
|View full text |Cite
|
Sign up to set email alerts
|

National Trends in Oral Antibiotic Prescribing in United States Physician Offices from 2009 to 2016

Abstract: BACKGROUND Prior studies have found that outpatient antibiotics are commonly prescribed for nonbacterial conditions. It is unclear if national prescribing has changed in recent years given recent public health and antimicrobial stewardship initiatives. This study aimed to describe antibiotic prescribing in United States (U.S.) physician offices. MATERIALS/METHODS This was a cross-sectional study of all sampled patient visits in the Centers for Disease Control and Prevention's National Ambulatory Medical Care S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
(78 reference statements)
0
12
0
Order By: Relevance
“…There was an important seasonal variation for both amoxicillin and azithromycin, with an increase in DDD in the colder months of the southern hemisphere (June, July, and August). Both amoxicillin and azithromycin have been widely used for respiratory infections, which occur more frequently in the coldest months of the year ( Young et al, 2020 ). The three most prescribed antibiotics in Brazil (cephalexin, azithromycin and amoxicillin) accounted for 2/3 of all prescriptions since 2014.…”
Section: Discussionmentioning
confidence: 99%
“…There was an important seasonal variation for both amoxicillin and azithromycin, with an increase in DDD in the colder months of the southern hemisphere (June, July, and August). Both amoxicillin and azithromycin have been widely used for respiratory infections, which occur more frequently in the coldest months of the year ( Young et al, 2020 ). The three most prescribed antibiotics in Brazil (cephalexin, azithromycin and amoxicillin) accounted for 2/3 of all prescriptions since 2014.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that, similar to observations in hospitals, clinicians may prescribe antibiotics to reduce the cognitive load associated with diagnostic uncertainties in patients with suspected infection. 33 As previously reported by Young et al, 24 the large proportion of antibiotics prescribed without an accompanying ICD code has notable implications for implementing antimicrobial stewardship in outpatient settings. It is possible that prescribers may include the rationale for antibiotic use in their clinical notes.…”
Section: Discussionmentioning
confidence: 79%
“…As observed in other studies that focus on patterns of antibiotic prescribing in the outpatient setting, >50% of patients in our cohort did not have an infectious disease diagnosis associated with their antibiotic prescriptions. 24,25 Given that millions of outpatient antibiotic prescriptions are issued annually 26 and that the impact of those prescriptions toward the emergence of antibiotic resistance can persist for months, the contribution of outpatient antibiotic exposure to the overall burden of antibiotic resistance is likely to be significant and grossly underestimated. R-GNB recognized via clinical cultures may be difficult to associate with a specific healthcare episode or antibiotic exposure because many are bacterial species that are commensal organisms in the gut microbiota; thus, the duration of colonization may be prolonged Furthermore, horizontal transmission of R-GNB and resistance determinants can occur even in the absence of antibiotic selective pressure.…”
Section: Discussionmentioning
confidence: 99%
“…A recent cross-sectional evaluation utilizing data from the Center for Disease Control (CDC) National Ambulatory Medical Care Survey (NAMCS) from 2009 to 2016 found that 11.3% of the 7 billion outpatient visits included were associated with at least 1 antibiotic prescription. 8 Antimicrobial prescriptions were further categorized in this study as appropriate, possibly appropriate or inappropriate based on ICD-10 codes and a general assessment of the need for antibiotic therapy (indicated, may be indicated, or not indicated, respectively). Of the 783 415 182 visits included, 55.9% of antibiotic prescriptions were identified as inappropriate and 35.7% as possibly appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Previous data has suggested that inappropriate prescribing may be more common among advanced practice providers compared to physicians in this population. 8 Additionally, we identified a high number of inappropriate antimicrobial prescriptions during 30-day visits related to GAS pharyngitis; data from the UCC may be extrapolated to the health-system at large and health-system wide interventions are likely necessary to improve care on a global level. When evaluating RADT availability and prescribing patterns related to GAS pharyngitis, a larger analysis including multiple locations (ie, multiple ambulatory sites, emergency department, etc.)…”
Section: Discussionmentioning
confidence: 99%